New oxymesterone metabolites in human by gas chromatography‐tandem mass spectrometry and their application for doping control. Issue 7 (22nd July 2015) - Yang, Sheng; Lu, Jianghai; Xu, Youxuan; Wang, Xiaobing
Abstract : Oxymesterone (17α‐methyl‐4, 17β‐dihydroxy‐androst‐4‐ene‐3‐one) is one of the anabolic androgenic steroids (AAS) banned by the World Anti‐Doping Agency (WADA). The biotransformation of oxymesterone is performed in vitro by human heptocytes and human urinary metabolic profiles are investigated after single dose of 20 mg to two adult males as well. Cell cultures and urine samples were hydrolyzed by β‐glucuronidase, extracted, and reacted with N‐Methyl‐N‐trimethylsilyltrifluoroacetamide (MSTFA), ammonium iodide (NH4 I), and dithioerythritol. After derivatization, a gas chromatography triple quadruple tandem mass spectrometry (GC‐MS/MS) using full scan and MS/MS modes was applied. The total ion chromatographs of the blank and the positive samples are compared, and 7 new metabolites were found. In addition to the well‐known 17‐epioxymesterone, oxymesterone is metabolized by 4‐ene‐reduction, 3‐keto‐reduction, 11β‐hydroxylation, and 16ξ‐hydroxylation. Based on the behavior of the MS/MS results of product ion and precursor ion modes, a GC‐MS/MS method has been developed monitoring these metabolites. The structures of metabolite 2 and 4 are tentatively identified as 17α‐methyl‐3β, 17β‐dihydroxy‐5α‐androstane‐4‐one and 17α‐methyl‐3α, 4ξ, 17β‐trihydroxy‐5α‐androstane, respectively. Detection of oxymesterone using new metabolites M2 and M4 can extend the detection window up to 4 days since the parent steroid was not detectable. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The metabolism of Oxymesterone is investigated in vitro and in vivo in humans. Seven new metabolites are tentatively identified using GC‐MS/MS techniques. M2 and M4 can extend 4 days since the parent drug no longer be detected.